Edukasi Hukum Penentuan Hak Waris Anak Di Bawah Umur Serta Peranan Pemerintah Dalam Penetapan Ahli Waris - Sri Wahyuni Laia; Dewi Ervina Suryani; Natasya Sabrina Kathlen Sihombing; Mesra Abadi Lase; Upi Indah Stevani Laoli (Annusfy : Journal of Multidisciplinary Research, 2026)
This community service program aims to enhance public understanding and legal awareness regarding minors’ inheritance rights and the role of government institutions in the formal determination of heirs. The program employed a Participatory Action Research (PAR) approach consisting of problem identification, educational planning, participatory legal counseling, and reflective evaluation. The results indicate a significant improvement in community knowledge of inheritance law systems, formal procedures for determining heirs through the court, and the protective role of village governments and related institutions. This initiative is expected to reduce inheritance conflicts, strengthen legal protection for minors, and promote a culture of legal awareness within the community.